Understanding how Asperger children and adolescents think and learn : creating manageable environments for AS students - Jacobsen, Paula (Jessica Kingsley, 2005)
Understanding How Asperger Children and Adolescents Think and Learn helps educators appreciate the learning process and improve its effectiveness for students with Asperger Syndrome. The author provides a compelling inside view of how AS pupils perceive and understand what goes on in the classroom, and how they, in turn, are perceived by fellow pupils and teachers. She adopts a pragmatic approach to improving communications in the classroom and offers practical intervention strategies to increase mutual understanding and create a rewarding and supportive learning environment. The book also inc.